The Effect of Local Coffee Commodities and Community-Based Tourism on Tourist Satisfaction in Nglinggo Tourism Village, Yogyakarta: The Mediating Role of Service Quality - Ariyanto, Ariyanto; Welsa, Henny; Lukitaningsih, Ambar (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study examines the impact of local coffee commodities and Community-Based Tourism (CBT) on tourist satisfaction in Nglinggo Tourism Village, emphasizing the mediating role of service quality. Adopting a quantitative explanatory design, the study collected data from 150 tourists through a structured Likert-scale questionnaire. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The findings indicate that local commodities, CBT, and service quality each have a positive and significant effect on tourist satisfaction. Moreover, service quality serves as a crucial mediating variable that strengthens the relationship between local commodities, CBT, and satisfaction outcomes. These insights are valuable for destination managers, policymakers, and CBT practitioners seeking to improve service standards, empower local communities, and enhance visitor experiences in village-based tourism. The novelty of this study lies in positioning service quality as an intermediary variable that bridges the cultural-economic contributions of CBT and local products with tourist satisfaction—an approach not widely explored in previous research on educational tourism destinations.